Optical tomography experimental setup : a study on reflection effect - Mohd Muji, Siti Zarina; Abdul Rahim, Ruzairi; Rahiman, Mohd Hafiz Fazalul; Mohamad, Elmy Johana (Penerbit UTM Press, 2011)
The selection types of material to be used as an obstacle or a sensor jig is really important before doing any decision about what material to be used in Optical Tomography. An experiment needs to be done to analyze the performance of each type of material. In this paper, the selection is between Aluminium and PVC (Polyvinyl chloride) whether they are suitable as an obstacle or more suitable for the sensor jig design. With the experiment, we can see the theory behind it, that showing the trustiness of the experiment that has been done.